Potato Nutritional Quality Loss Due to Bruising: Need Attention During Handling - Kaundal, Bandana; Sharma, Vineet; Singh , Sukhwinder; Singh, Brajesh; Kumar, Manoj (Food Science and Engineering, 2022)
Bruising of potatoes is the main problem in potato processing industry and is the major cause of consumer dissatisfaction in terms of economic loss. Potato quality is adversely affected by bruise damage. In general practice, when tubers are harvested, handled, packed and transported, it is impossible to prevent them from falling and damage. After falling, external symptoms sometimes are not visible but the damage may affect the nutritional quality. Sorting and grading contribute 0.98 kilograms per quintal giving a percentage of 16.50%. Packaging and storage yield 0.45 and 1.18 kilograms per quintal owing 7.49 and 19.79% respectively. Therefore, the aim of the experiment was to find out the effect of bruising on processing and nutritional quality of processing varieties viz. Kufri Chipsona-1, Kufri Chipsona-3, Kufri Frysona and table purpose varieties viz. Kufri Surya and Kufri Pukhraj by simulating different impacts (control, 30, 60 and 90 cm). Results revealed that all processing varieties resulted in deterioration of chip score due to an increase in reducing sugars concentration after impact (45 and 60 days of storage, ambient storage). Weight dropping to potato tubers from a height of 60 cm and 90 cm and their storage up to 60 DOS (days of storage) gave comparably high reducing sugars. Impact from a height of 30, 60 and 90 cm, irrespective of all the varieties reported having higher phenol content. Reduction in weight loss was directly proportional to the height of impact and quality deteriorated further during storage. Mechanical damage to cell walls, caused loss of quality through texture softening, followed by decreasing texture firmness of potato.